Penerapan Keadilan Restoratif terhadap Penyalahguna Narkotika pada Tahap Penuntutan - Damayanti, Tarisa; Ravizki, Eka Nanda (Jurnal Media Justitia Nusantara, 2024)
This study aims to explore the application of restorative justice to narcotics abusers in the prosecution process in order to see the embodiment of the theory of legal effectiveness. The type of research used is empirical juridical, with a qualitative approach. Data sourced from primary and secondary data. The data collection method was carried out by interviews and observations at the Sidoarjo District Attorney's Office, as well as a library study. Data analysis used descriptive analytical method. The results of the study show that its application is basically in accordance with the Attorney General's Guidelines Number 18 of 2021 concerning Settlement of Handling Cases of Narcotics Abuse through Rehabilitation with a Restorative Justice Approach as the Implementation of the PrinciplesMr. Litis Prosecutor. However, the existence of a concept of restorative justice that is not yet firm until problems are encountered in implementation shows that the effectiveness of the law has not been realized properly.